An open-label prospective randomized multicenter study of intensive versus weekly granulocyte and monocyte apheresis in active crohn's disease. Issue 1 (December 2015) - Yoshimura, Naoki; Yokoyama, Yoko; Matsuoka, Katsuyoshi; Takahashi, Hiroki; Iwakiri, Ryuichi; Yamamoto, Takayuki; Nakagawa, Tomoo; Fukuchi, Takumi; Motoya, Satoshi; Kunisaki, Reiko; Kato, Shingo; Hirai, Fumihito; et al.
Abstract Background Granulocyte and monocyte adsorptive apheresis (GMA) has shown efficacy in patients with active Crohn's disease (CD). However, with routine weekly therapy, it may take several weeks to achieve remission. This study was performed to assess clinical efficacy and safety of intensive GMA in patients with active CD. Methods In an open-label, prospective, randomized multicentre setting, 104 patients with CD activity index (CDAI) of 200 to 450 received intensive GMA, at two sessions per week (n = 55) or one session per week (n = 49). Clinical remission was defined as a CDAI score <150. Patients in each arm could receive up to 10 GMA sessions. However, GMA treatment could be discontinued when CDAI decreased to <150 (clinical remission level). Results Of the 104 patients, 99 were available for efficacy evaluation as per protocol, 45 in the weekly GMA group, and 54 in the intensive GMA group. Remission was achieved in 16 of 45 patients (35.6 %) in the weekly GMA and in 19 of 54 (35.2 %) in the intensive GMA (NS). Further, the mean time to remission was 35.4 ± 5.3 days in the weekly GMA and 21.7 ± 2.7 days in the intensive GMA (P = 0.0373). Elevated leucocytes and erythrocyte sedimentation rate were significantly improved by intensive GMA, from 8005/μL to 6950/μL (P = 0.0461) and from 54.5 mm/hr to 30.0 mm/hr (P = 0.0059), respectively. In both arms, GMA was well tolerated and was without safety concern. Conclusions In this study, with respect to remission rate, intensive GMA was not superior to weekly GMA, but the time to remission was significantly shorter in the former without increasing the incidence of side effects. UMIN registration # 000003666.